ASPEK MORAL DALAM NOVEL SAMAN KARYA AYU UTAMI (SEBUAH PENDEKATAN SOSIOLOGI SASTRA) - Ana Rosmiati (Institut Seni Indonesia Surakarta, 2006)
Novel Saman Ayu Utami masterpiece represent a novel which dare to express problem of epoch by various cultural information traffic and also event. This novel represent categorized novel nicely so that become Romance Council sayembara winner Artistry onakarta. In this article of dkupas hit various problem ofthat good moral of powermoral and authority, political moral, religious moral, assocciation moral, and culturalmoralKeyword ; Moral